Characterization of the complete plastid genome of Gaultheria griffithiana (Ericaceae). Issue 5 (4th May 2021) - Li, Yi-Rong; Xu, Yan-Ling; Du, Xin-Yu; Yang, Shu-Da; Lu, Lu
Abstract: Gaultheria griffithiana is an evergreen shrub in the family Ericaceae. It is used as a source of the Chinese traditional medicine, Tougucao, with distribution of the junction of eastern Himalaya and Hengduan Mountain. The chloroplast genome of G. griffithiana is 175, 649 bp in length with 135 genes, including eight rRNA genes, 39 tRNA genes, and 85 protein-coding genes. Phylogenetic analysis has converged on the placement of G. griffithiana as sister to G. praticola, G. nummularioides, and G. hookeri within the Leucothoides clade of Gaultheria in this study.